FORMULASI KEBIJAKAN PENERAPAN SISTEM ELECTRONIC ROAD PRICING (ERP) PEMERINTAH PROVINSI DKI JAKARTA - Teguh Saeful Hamzah; Teguh Kurniawan (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2024)
The rapid growth of private vehicle ownership and traffic has prompted the government to implement the Electronic Road Pricing (ERP) policy in controlling the level of congestion in DKI Jakarta. This research method involves a literature review and case studies using qualitative descriptive methods and secondary data to find out how to formulate ERP implementation policies in DKI Jakarta. The results of the analysis show that sustainable policy formulation in the ERP planning cycle will result in holistic and inclusive regulations, as well as strengthen the commitment of relevant stakeholders in the implementation of ERP policies in DKI Jakarta.